Spatial patterns of medium and large size mammal assemblages in várzea and terra firme forests, Central Amazonia, Brazil - Alvarenga, Guilherme Costa; Ramalho, Emiliano Esterci; Baccaro, Fabrício Beggiato; da Rocha, Daniel Gomes; Ferreira-Ferreira, Jefferson [UNESP]; Dineli Bobrowiec, Paulo Estefano (Public Library of Science (PLoS), 2018)
Várzea forests account for 17% of the Amazon basin and endure an annual inundation that can reach 14 m deep during 6–8 months. This flood pulse in combination with topography directly influences the várzea vegetation cover. Assemblages of several taxa differ significantly between unflooded terra firme and flooded várzea forests, but little is known about the distribution of medium and large sized terrestrial mammals in várzea habitats. Therefore, our goal was to understand how those habitats influence mammalian species distribution during the dry season. Specifically, we: (1) compared the species composition between a terra firme (Amanã Sustainable Development Reserve) and a várzea forest (Mamirauá Sustainable Development Reserve); and (2) tested the influence of the várzea habitat classes on the number of records, occurrence and species composition of mammalian assemblages. The sampling design in each reserve consisted of 50 baited camera trap stations, with an overall sampling effort of 5015 camera trap days. We used Non-Metric Multidimension Scaling (NMDS) to compare species composition between terra firme and várzea forests, and used Generalized Linear Models (GLM) to assess how habitat types and a habitat diversity index affect mammal distributions. We recorded 21 medium and large sized mammalian species, including 20 species in terra firme and only six in várzea (3443 records). Flood pulse and isolation in várzea forest drove the dissimilarity between these two forest types. In várzea forest, medium size mammals, in general, avoided habitats associated with long flooding periods, while jaguars (Panthera onca) appeared to prefer aquatic/terrestrial transition zones. Habitats that remain dry for longer periods showed more mammalian occurrence, suggesting that dispersion via soil is important even for semi-arboreal species. This is the first study to evaluate differential use of várzea habitats by terrestrial mammalian assemblages.